2022
DOI: 10.3390/ijms232012209
|View full text |Cite
|
Sign up to set email alerts
|

Altered Circulating Follicular T Helper Cell Subsets and Follicular T Regulatory Cells Are Indicators of a Derailed B Cell Response in Lupus, Which Could Be Modified by Targeting IL-21R

Abstract: Systemic lupus erythematosus (SLE) is characterized by the breakdown of self-tolerance, the production of high-affinity pathogenic autoantibodies and derailed B cell responses, which indicates the importance of central players, such as follicular T helper (TFH) subsets and follicular T regulatory (TFR) cells, in the pathomechanism of the disease. In this study, we aimed to analyze the distribution of the circulating counterparts of these cells and their association with disease characteristics and B cell dispr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
1
3
0
Order By: Relevance
“…Previous studies have reported an increased frequency of cTfh cells in several autoimmune diseases, including SLE. 3,4,23,24 In this study, we also found a higher frequency of cTfh cells in SLE patients than in HS. Moreover, we showed that patients with clearly active disease had increased cTfh cells than patients with mildly active/nonactive disease.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have reported an increased frequency of cTfh cells in several autoimmune diseases, including SLE. 3,4,23,24 In this study, we also found a higher frequency of cTfh cells in SLE patients than in HS. Moreover, we showed that patients with clearly active disease had increased cTfh cells than patients with mildly active/nonactive disease.…”
Section: Discussionsupporting
confidence: 79%
“…Compared with healthy people, the proportion of cTfh17 cells in SLE patients is increased [37]. However, Szabó et al found that the frequency of cTfh17 cells decreased in patients with lupus nephritis, which is related to higher disease activity scores [38]. These different results may be due to the use of different markers to detect cTfh17 cells.…”
Section: Tfh and Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Its receptor IL-21R is abundantly expressed in a variety of immune cells. 118,119 Importantly, a study by Zhou t al. in 2023 showed that IL-21 has prominent antitumor effects in tumors.…”
Section: Combination Of Anti-pd-1/pdl1 and Anti-ctla-4 Therapy To Tre...mentioning
confidence: 99%
“…IL‐21 belongs to the common γ‐chain (γc) receptor cytokine family. Its receptor IL‐21R is abundantly expressed in a variety of immune cells 118,119 . Importantly, a study by Zhou t al.…”
Section: Combination Icp Inhibitor Therapies To Treat Hccmentioning
confidence: 99%